PELAYANAN KESEHATAN MASYARAKAT MASA PANDEMIK COVID-19 DAN SESUAI SUDUT PANDANG ISLAM - Saifuddin Zuhri; Diana Amalia (Jurnal Penelitian Administrasi Publik, 2021)
This journal set in at examining the correlation between Islamic values and public services. Theoretically, the finding were expected to yield the proof that there was some positive relation between organizational culture, especially in religious values and performance of organization that refers to quality of public services. And now the Covid-19 outbreak is not only a national problem but it is getting to be a global problems. The spread of Covid-19 is so fast and lethal, where the transmission can be through physical contact from the mouth, eyes, and nose. To avert the spread of this Covid-19 outbreak, it needed the contribution of government, religious leader to help another, communities, help each other and remind one another to deepen about Covid-19. This research using literature research method, which is from collecting interview data and observation of many sources. And for data analysis uses qualitative analysis by three steps : reduction, serving, and verification of all the data. In connextion to medical procedure and surgical technique also pharmacology (the dosage and type of medicine, its islamisation is run into by following medical and pharmaceutical science, and also the perfection of medical technology. Keywords : Public Service, Islamic Healthcare, Covid-19, Indonesia.